2015
DOI: 10.1111/den.12420
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of pediatric post‐transplant biliary complications is safe and effective

Abstract: BC in pediatric LT were treated safely and successfully in pediatric patients when the biliary tract was accessible. The most common complications were AST, BCS and ITBL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
(61 reference statements)
1
17
0
1
Order By: Relevance
“…In our series, patients required a median of three interventions over the median period of 9.1 months. Dechene et al reported 11 children with ABS. Endoscopic treatment was successful in 100% with a major complication rate of 9%, and a median of four treatment sessions was required until resolution of stricture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our series, patients required a median of three interventions over the median period of 9.1 months. Dechene et al reported 11 children with ABS. Endoscopic treatment was successful in 100% with a major complication rate of 9%, and a median of four treatment sessions was required until resolution of stricture.…”
Section: Discussionmentioning
confidence: 99%
“…The most common are pancreatitis with the incidence varying between 2.7 and 12.5%, cholangitis occurring between 3.3 and 7.7% and bleeding after sphincterotomy between 1.6% and 23.5% …”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was revealed by Dechene et al . in their series of seventeen patients. However, this series also reported ischaemia‐type biliary lesions and more importantly a relatively higher incidence of biliary casts.…”
Section: Discussionmentioning
confidence: 99%
“…This is more relevant in the context of not only living donor LT but also with split and technical‐variant grafts . ERCP has been shown to be a safe and effective intervention tool for both diagnosis as well as simultaneous therapeutic management of biliary complications post‐LT . Experience in children post‐LT, although described earlier, is limited and mainly from the West .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, biliary complication rates following liver transplant vary from 12 % to 50 % [1], and anastomotic strictures occur in up to 10 % of patients [2]. Whereas the utility of endotherapy in the adult population is well documented, data are limited for similar interventions in the cohort of pediatric patients with liver transplants [3]. The placement of a fully covered self-expanding metal stent is an emerging modality for the treatment of refractory biliary strictures following liver transplant [4].…”
mentioning
confidence: 99%